546b + (a - b) * 26 = 546b + 26a - 26b = 520b + 26a
b = 2 и a = 6
520 * 2 + 26 * 6 = 1040 + 156 = 1196
(d + c) * 34 - 42d = 34d + 34c - 42d = 34c - 8d
c = 5 и d = 7
34 * 5 - 8 * 7 = 170 - 56 = 114
Пошаговое объяснение:
ответ:76d+34c
34*d+34*c-42d
546b + (a - b) * 26 = 546b + 26a - 26b = 520b + 26a
b = 2 и a = 6
520 * 2 + 26 * 6 = 1040 + 156 = 1196
(d + c) * 34 - 42d = 34d + 34c - 42d = 34c - 8d
c = 5 и d = 7
34 * 5 - 8 * 7 = 170 - 56 = 114
Пошаговое объяснение:
ответ:76d+34c
Пошаговое объяснение:
34*d+34*c-42d